2021
DOI: 10.1016/j.nmni.2021.100907
|View full text |Cite
|
Sign up to set email alerts
|

Case report: a rare case of NOMA (cancrum oris) in a Malian woman

Abstract: Noma or cancrum oris is a multi-bacterial and opportunistic infection that destroys soft tissue, as well as muscle and bone, and can be fatal. We present a rare case of Noma in a 32-year-old Malian woman, from whom we isolated an Escherichia coli extended-spectrum beta-lactamase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Despite significant progress in scientific methods since these ancient reports, the literature on noma has predominantly been comprised of low level evidence such as case reports [10]. The focus of recent literature on noma (2019-2021) includes noma's distribution and risk factors [17][18][19], treatment [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], knowledge and beliefs about the disease [14,[35][36][37] along with reviews of the literature and viewpoints [38][39][40][41]. Recent literature (2019-2021) has shown that noma cases are being reported from an increasingly diverse set of geographical locations outside of Africa including China [22,28], India [23], Vietnam, [24] and Indonesia [33] (Fig.…”
Section: Neglect Of Noma Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite significant progress in scientific methods since these ancient reports, the literature on noma has predominantly been comprised of low level evidence such as case reports [10]. The focus of recent literature on noma (2019-2021) includes noma's distribution and risk factors [17][18][19], treatment [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], knowledge and beliefs about the disease [14,[35][36][37] along with reviews of the literature and viewpoints [38][39][40][41]. Recent literature (2019-2021) has shown that noma cases are being reported from an increasingly diverse set of geographical locations outside of Africa including China [22,28], India [23], Vietnam, [24] and Indonesia [33] (Fig.…”
Section: Neglect Of Noma Researchmentioning
confidence: 99%
“…As such, the goal of noma surgery is to improve function where possible and the quality of life of the survivor. Recent studies have shown that a range of methods are used to treat noma cases, and that although prenoma functionality is not often restored, surgical treatment does improve patients' quality of life [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Specific improvements included decreased social isolation and improved functionality such as eating and speaking [31].…”
Section: Normal Anatomy Not Restoredmentioning
confidence: 99%